Tamråttan (Rattus norvegicus domesticus) och möjligheten att tillgodose dess behov - Lind, Frida (SLU/Dept. of Animal Environment and Health (until 231231), 2019)
This study aimed to investigate if the selection of rat related products found in pet stores coincide with the natural behaviours of the domestic rat (Rattus norvegicus domesticus). Literature regarding the wild brown rat (Rattus norvegicus) and the wild black rat (Rattus rattus) were researched to some extent to be able to draw parallels to and learn about the needs and behaviours of the pet rat. It was also of interest to investigate how much knowledge the staff working in the animal stores possessed. The methods used in this study consisted by a survey sent out to rat related groups on Facebook, researching the general experiences for the common rat owners regarding the accessibility of rat related products in stores. This part of the study also covered how rat owners experienced the level of knowledge from the animal store staff workers. The second method used was a field study where 4 different animal stores were visited and inventory was taken, focusing on toys for enrichment, information, gnawing material, fodder, cage furniture, cages and bedding material. Results showed that most of the rat owners participating in the study were of the opinion that a lot of the above-mentioned products were accessible in stores, although they replied having a preference for ordering most products online. The field study showed that although there were few species-specific products for rats, plenty of products for other species also appears to be suitable for rats - especially cage furniture made for rats and ferrets. However, scientific literature indicates that cage furniture and bedding made from certain materials, especially wood made out of pine, might be toxic to rats and should be avoided as far as possible. It is reasonable to draw the conclusion that if a product is originally made for some other species it makes sense to do some research about the material, to make sure it is completely rat safe. The most prominent thing lacking in stores were easily accessible information, something that should be added to the selection since it would most likely help a lot of rat owners navigate through the different products and materials available on the market.